Implementation of PMA Number 73 of 2022 at PTKIN: A Study of the PPKS Task Force at UIN Sunan Gunung Djati Bandung - Anita Fitriyani Rahayu; Yasmin Putri Ananda; Abdal (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
AbstractThis study analyzes the implementation of Minister of Religious Affairs Regulation No. 73 of 2022 concerning the Prevention and Handling of Sexual Violence (PPKS) at UIN Sunan Gunung Djati Bandung through the PPKS Task Force, using George C. Edward III’s policy implementation theory, which encompasses communication, resources, disposition, and bureaucratic structure. The study employs a descriptive qualitative approach through in-depth interviews and document analysis, with informants selected through purposive sampling. The findings indicate that policy implementation has been carried out through existing institutional mechanisms; however, challenges remain in the areas of communication and resources, particularly limited human resources, low participation of peer counselors, and delays in budgetary and facility support. Disposition emerged as the strongest aspect, reflected in the commitment of implementers, competency-based selection, and a humanistic approach. Meanwhile, the bureaucratic structure has been formally established, although challenges regarding institutional independence persist. Overall, the implementation of Minister of Religious Affairs Regulation No. 73 of 2022 at UIN Bandung has been implemented reasonably well, but further strengthening is needed in the areas of communication, resources, and bureaucratic structure.Keyword: George C. Edward III, Policy Implementation; PPKS; PPKS Task Force; State Islamic Higher Education Institutions (PTKIN)